Amazigh in Morocco through the Lens of the U.S. State Department's Reports between 1999 and 2020: A Critical Discourse Analysis - Brahim Ait Laaguid (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This paper uses critical discourse analysis (CDA), particularly Theo Van Leeuwen's socio-semantic inventory, to discover the discursive representations of the social actors in the U.S. State Department's coverage of Amazigh struggle for their linguistic and cultural rights in its annual reports on human rights practices in Morocco, between 1999 and 2020. The data comprises 21 texts with 5796 words. These are the content of the National/ Racial/ Ethnic Minorities section within the pertinent reports, available on the State Department's online database. The investigated section follows the section of Persons with Disabilities. The findings show that the Amazigh issue has not been reported with careful attention; inaccurate information has, for instance, been detected. The inclusion representational categories are predominantly used; differentiation and categorization are given special weight, compared to the strategies of genericization, individualization, objectivation, and assimilation. Assigning distinctive prominence to two groups aims to emphasize the persistent conflict in Morocco between the disempowered Amazigh activists and the empowered Moroccan authorities. The exclusion representational categories, on the other hand, specifically backgrounding and nominalization, are also heavily employed to mystify agency in critical situations, mainly when the related social actors are the authorities. The study concludes that the representation of the social actors is influenced by the ideological stances and agenda of the U.S. State Department.